PENGARUH RELAKSASI OTOT PROGRESIF TERHADAP PENURUNAN TINGKAT INSOMNIA PADA LANSIA - Antoni, Adi; Rangkuti, Gumantri Rizky; Martua, Tohong (Jurnal Kesehatan Ilmiah Aufa Royhan, 2016)
Insomnia is common sleep disorder in elderly. The aims to find "Effect of Progressive Muscle Relaxation Rate Of Decline In Elderly Insomnia". This study uses a quasi-experimental design with nonequivalent control group pretest-postest design. The sample in this study were 50 respondents among the 25 people who control group and intervention group 25. Sampling technique used is purposive sampling. Where the results of the study showed that in the control group before giving an average mean 27.20. the value of the minimum 21 and maximum 32 intervention. After administration of intervention control group was 32.72 its minimum value 28, and the maximum 36. Selisi mean of the results above,5.52, and the results obtained showed that the intervention group before giving the average mean of 35.60, the value of minimum 34 and maximum 44. After Award intervention intervention group average mean is 28:88 its minimum value 28 and maximum 32. andselisi mean of the results above, 8:32. The results of statistical tests on the data obtained (mean rank) the level of insomnia before the intervention in the intervention group was 35.60, and the data in the control group (mean rank) 27.20, P = 0.490 on the alpha (α) of 5%. Statistical test results in the data obtained (mean rank) the level of insomnia in both groups after intervention was for the intervention group and the control group 32.72 28.88 selisi mean 6.2, p = <0.0001 on the alpha (α) of 5%. From the analysis of statistical significance value < 0001 it can be concluded that there is a significant influence on the level of insomnia after a given intervention in the form of progressive muscle relaxation.